Maternal Health Literacy and Exclusive Breastfeeding Intention: A Theory of Planned Behaviour Study in Antenatal Care - Abiola Adiat Omokhabi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study examined the joint and independent contributions of maternal health literacy, attitudes toward exclusive breastfeeding, subjective norms, and perceived behavioural control to exclusive breastfeeding intention among pregnant women attending antenatal care in Ibadan North Local Government Area, Nigeria. The study extended the Theory of Planned Behaviour by incorporating maternal health literacy as an additional cognitive predictor. A facility-based cross-sectional survey was conducted among 181 third-trimester pregnant women recruited through convenience sampling from three Primary Health Centres in Idi-Ogugu (Agodi-Gate), Agbowo, and Oke-Apon (Yemetu). Data were collected from July to December 2025 using a modified Maternal Health Literacy and Pregnancy Outcome Questionnaire, Theory of Planned Behaviour-based measures, and the Infant Feeding Intentions Scale. Descriptive statistics and multiple linear regression were used for analysis. Participants had a low level of maternal health literacy, with an overall weighted mean of 1.98. The regression model was statistically significant (R = 0.455, R² = 0.207, adjusted R² = 0.189, F(4,176) = 11.467, p < 0.001) and explained 20.7% of the variance in exclusive breastfeeding intention. Maternal health literacy (β = 0.345, p = 0.002) and attitudes toward exclusive breastfeeding (β = 0.210, p = 0.033) were significant positive predictors, whereas subjective norms and perceived behavioural control were not significant independent predictors. These findings highlight the importance of strengthening maternal health literacy and promoting favourable breastfeeding attitudes through accessible, culturally appropriate antenatal education.